2021
DOI: 10.1155/2021/1173603
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength and Microstructure of Intact Loess Subjected to Freeze‐Thaw Cycling

Abstract: In the Loess Plateau, seasonal freeze and thaw cause great damage to the mechanical behavior and microstructure of soil, which leads to frequent geological disasters during winter and spring. To investigate the influence of freeze-thaw (FT) cycling (FTC) on the shear strength and microstructure of intact loess, triaxial shear, nuclear magnetic resonance, and scanning electron microscope tests were carried out on soil samples after target FT cycles. The results indicate that the FTC has limited changes to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…During FT cycles, the fragmentation and reorganization of loess particles lead to structural damage, and the development of internal pore space in the soil. With increasing cycles, the loss of the peak strength of loess gradually increases, and the shear strength continues to decrease and eventually approaches a residual value [12,13]. Due to extreme cold and abnormal drought, loess in Northwest China is always under the coupling action of alternating dry and wet and repeated freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 99%
“…During FT cycles, the fragmentation and reorganization of loess particles lead to structural damage, and the development of internal pore space in the soil. With increasing cycles, the loss of the peak strength of loess gradually increases, and the shear strength continues to decrease and eventually approaches a residual value [12,13]. Due to extreme cold and abnormal drought, loess in Northwest China is always under the coupling action of alternating dry and wet and repeated freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21]. Liu et al showed that the FTCs had a limited impact on the change in the soil stress-strain curve, but they significantly attenuated the peak deviation stress [22]. Li et al studied the changes in the stress and strain before and after freezing and thawing and believed that the interior strength of the soil structures was significantly affected by the FT impacts [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of global climate change, influenced by geographical location, soil texture, and climate, the region exhibits significant seasonal FT from late autumn to early spring each year (Bo et al, 2021). Numerous studies have revealed that the effects of FT cycling processes on soil properties in different areas of the Loess Plateau vary depending on the type of vegetation (Ye and Li, 2018;Wang et al, 2019;Bo et al, 2021;Liu et al, 2021a). Studies have shown that arboreal land soils freeze later than bare land (Bo et al, 2021) and that dam farmland was better able to retain soil moisture during FT, resulting in higher water migration and increment in the soil than slope farmland (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that arboreal land soils freeze later than bare land (Bo et al, 2021) and that dam farmland was better able to retain soil moisture during FT, resulting in higher water migration and increment in the soil than slope farmland (Wang et al, 2019). Other studies have shown that FT cycling processes weaken soil shear strength (Liu et al, 2021a) and disrupt the internal soil microstructure (Ye and Li, 2018;Liu et al, 2021a), which in turn affects soil carbon stocks and carbon cycling processes in the region (Bo and Brandt, 2003;Li et al, 2019;Xiao et al, 2019). Over the past few decades, a project known as "the Conversion of Farmland to Forests and Grasses Program" has been put into place in this region to efficiently manage soil erosion and realize ecological restoration and its virtuous cycle (Yang et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%